Evidence of Alfvénic Activity in Jupiter's Mid‐To‐High Latitude Magnetosphere. Issue 6 (26th May 2022) - Lorch, C. T. S.; Ray, L. C.; Wilson, R. J.; Bagenal, F.; Crary, F.; Delamere, P. A.; Damiano, P. A.; Watt, C. E. J.; Allegrini, F.
Abstract: Using a combination of Juno magnetometer and plasma data, we show evidence of Alfvénic turbulence within the mid‐to‐high latitude magnetosphere with sufficient conditions to trigger auroral particle acceleration. We analyze 12 events that, in agreement with theoretical results, are found to be dissipative at the electron inertial scale. Furthermore, these events contain significant Poynting flux in the range ∼0.8–20 mW/m 2 at ionospheric altitudes. This is sufficient to generate auroral emissions. We confirm that such events are incompressible, confirming their Alfvénicity, occur at dissipative scales, have intermittent features present and are multifractal in nature. These results illustrate the importance of turbulence in the mid‐to‐high latitudes of Jupiter's magnetosphere as a driver of particle acceleration. Plain Language Summary: Jupiter's aurora is the most powerful in the solar system. Electrons entering the upper atmosphere create these auroral displays, which were originally thought to be generated through a similar mechanism to those at Earth, via semi‐stationary electric fields aligned with the magnetic field close to the planet. However the Juno spacecraft in orbit around Jupiter, found much less instances of inverted V electron precipitation (driven by quasi‐static potential drops) than expected, therefore other mechanisms are needed along the magnetic field to provide electrons with the necessary energy to enter the planetary atmosphere. Before Juno it was not possible to gather in situ data in these regions. In this paper, we use Juno data to look in these regions for possible acceleration mechanisms and find that turbulence in the magnetic field has the potential to supply the required energy for auroral particle excitation. These results illustrate the importance of magnetic turbulence in Jupiter's space environment. Key Points: New observations of Alfvénic activity in mid‐high latitude regions of Jupiter's magnetosphere Events are turbulent in nature and are energy dissipative at the electron inertial scale Calculated Poynting flux of turbulent perturbations is sufficient to drive auroral emissions